PENGARUH WAKTU FERMENTASI TERHADAP PERSENTASE PENYISIHAN CHEMICAL OXYGEN DEMAND (COD) CAMPURAN LIMBAH CAIR INDUSTRI TAPIOKA DAN AIR - Umayi Belladiana, Wan Rizki Ansari, Setiaty Pandia (Universitas Sumatera Utara, 2014)
Study about the effect of fermentation time on the percentage removal of chemical oxygen demand (COD) a mixture of tapioca liquid industrial waste and water that aims to determine the effect of water quality and quantity of bio-gas generated from tapioca industrial wastewater combined with water. The research was conducted by combining tapioca industrial wastewater with water on several compositions, namely 100: 0; 85:15; 65:35; 50:50; 35:65; 15:85 (v / v) with cow dung starter in the batch anaerobic digester systems for 24 days with a neutral pH. The optimum percentage of allowance for COD at the ratio of tapioca liquid industrial waste and water at 15:85 with a value of 42.14% where the value of COD on day 0 was 1723 mg / L after day 24 was 997 mg / L .